Evaluation of the effect of dabrafenib and metabolites on QTc interval in patients with BRAF V600–mutant tumours. (23rd January 2018) - Nebot, Noelia; Arkenau, Hendrik‐Tobias; Infante, Jeffrey R.; Chandler, Jason C.; Weickhardt, Andrew; Lickliter, Jason D.; Sarantopoulos, John; Gordon, Michael S.; Mak, Gabriel; St‐Pierre, Annie; Tang, Lihua; Mookerjee, Bijoyesh; et al.
Abstract : Aims: The effect of repeat oral supratherapeutic dosing of the BRAF inhibitor dabrafenib on QTc interval was assessed in patients with BRAF V600–mutant tumours. Methods: Part 1 of this phase 1, multicentre, 2‐part study (BRF113773/NCT01738451) assessed safety/tolerability of dabrafenib 225 or 300 mg twice daily (BID) to inform part 2 dosing. Patients in part 2 received dabrafenib‐matched placebo on day −1, single‐dose dabrafenib 300 mg on day 1, 300 mg BID on days 2 to 7, and 300 mg on day 8 (morning), followed by 24‐h Holter electrocardiographic monitoring and pharmacokinetics sample collection each dose day. Pharmacokinetics/pharmacodynamics analysis assessed combined dabrafenib and metabolite effects on QTc interval. Results: Part 1 ( n = 12) determined supratherapeutic dosing, 300 mg BID, for part 2. Thirty‐one patients completed part 2. Mean maximum ΔΔQTcF occurred on day 8, 10 h postdose (2.86 msec; 90% CI, −1.36 to 7.07). Categorical analysis showed no placebo and dabrafenib outliers (increase >60 msec; QTcF >500 msec). Day 1 dabrafenib 300 mg C max and AUC(0–∞) were ≈ 2‐fold higher than with single‐dose 150 mg. Day 8 AUC(0‐τ) with 300 mg BID was ≈ 2.7‐fold higher than with 150 mg BID. Dabrafenib metabolites showed similar trends. Pharmacokinetics/pharmacodynamics modelling/simulation showed that median QTc increase was <5 msec (upper 90% CI, <10 msec). No unexpected toxicities occurred with supratherapeutic dosing. Conclusion: Repeat oral supratherapeutic dabrafenib 300 mg BID dosing had no clinically relevant effect on QTc interval, with no new safety signals seen.